Analisis sektor ekonomi di kabupaten malinau - Nella Rissa (INOVASI, 2016)
This study purposed to analyze yhe economic sector in Malinau District, which is analyzing basic sectors and non-basic, analyzing the rate of growth and competitiveness of the economic sectors in the Malinau District. Data were obtained from Produk Domestik Regional Bruto (PRDB) based on Constant Price in year of 2000 in the Malinau District and Province of East Borneo-North Borneo the year of 2009-2013. Data were analysed using the analisis method Location Quotient (LQ) and Shift  Share. The results showed that during the analysis period in year of 2009-2013 concluded each sector have their respective advantages both basic and non-basic, rate of fast growth and slow, and has strong competitiveness and weak. It is known that the basic sectors (superior) in Malinau District are the sector of Agriculture, Forestry and Fisheries, the sector of Mining and Quarrying and the Sector of Building. The sectors which have fast growth rate are the Sector of Agriculture, Forestry and Fisheries, the Sector of Electricity, the Sector of Gas and Water, Building, the Sector of Trade, Hotels and Restaurants, the Sector of Transportation and Communications, the Sectors of Services. Almost all sectors have the strong competitiveness, except the sector of Agriculture, Forestry and Fisheries that has weak competitiveness.Keyword: Location Qoutient, Shift Share, Sektor Ekonomi Produk Domestik Regional Bruto